Knowledge and awareness of cervical cancer and its prevention among nursing staff of a tertiary care teaching institute in South India - Dhodapkar, Sneha Badwe; Chauhan, Ramesh Chand; Thampy, Shilpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the second leading cause of morbidity and mortality among the females worldwide. India has the highest burden of cervical cancer patients, accounting for approximately one-fifth of the cases in world. Nurses being an important link between the doctors and female patients in OPD or wards, it is imperative that they should be aware of the facts about cervical cancer and especially of screening techniques which can be utilized in low-resource settings. Methods: A cross-sectional interview based study was done among 200 nurses of a tertiary care teaching institute from June 2013 to July 2013, to assess the knowledge and awareness of nursing staff regarding causes of cervical cancer and its prevention and early detection. Results: Among all participated nurses, 85% (n=170) were aware of the term cancer cervix and 45% reported that it is the most frequent gynaecological cancer in India. Only 30.6% reported that it is the leading cause of death among women due to cancer. Young age at first intercourse, multiple sex partners, cigarette smoking, high parity and lower socio-economic status were correctly responded by 13%, 48%, 16%, 9% and 13% of participants respectively, as risk factors for cervical cancer. None of the participants knew about the VIA method of screening for cervical cancer. Among 119 of those participants who knew that cervical cancer can be detected by Pap smear, only 5 (4%) had ever undergone Pap smear examination. Conclusions: Nurses identify certain aspects of cervical cancer correctly but their knowledge is not adequate, hence necessary changes should be made in their curriculum.